ANALISIS EKOSISTEM INDUSTRI ANIMASI LAYAR LEBAR STUDI KASUS: "SI JUKI THE MOVIE PANITIA HARI AKHIR" - Mazaya Muftiya Al Farabi; Hafiz Aziz Ahmad; Dwinita Larasati (Wimba : Jurnal Komunikasi Visual, 2022)
Indonesia has the potential in the field of creative economics especially animation. Although its contribution to GDP is only 0.17%, the film, animation & video sub-sector is among the three sub-sectors with the highest growth of 10.09%. The least contribution to GDP is because the animation industry ecosystem has not been well developed. One of the steps that can be taken to build an animation industry ecosystem is learning from the animation industry that is considered successful. "Si Juki The Movie Panitia Hari Akhir" widescreen animation is considered as successful animation because it is able to become box office animation by breaking the number of spectators' record for Indonesian-produced widescreen animations and has a complete journey like anime.The purpose of this study is to map the core business of widescreen animation industrial ecosystem "Si Juki The Movie Panitia Hari Akhir". This study uses qualitative research methods with a case study approach. Data collection uses literature studies, interviews and audio videos. From this research it is known that in Si Juki The Movie widescreen animation ecosystem, core business consists of "Faza" as Si Juki's IP creator, "Falcon Picture" as the producer and "Kumata Animation Studio" as the studio that produces Si Juki The Movie widescreen animation. Each core business builds a broader partnership called extended enterprise. The results of "Si Juki's The Movie Panitia Hari Akhir" animation movie ecosystem analysis can developed into a animation movie industrial ecosystem model.